PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN DENGAN BUDAYA KOLEKTIVITAS SEBAGAI VARIABEL MODERASI - Sudiharto, Agus -; Widajanti, Erni - (Universitas Slamet Riyadi, 2012)
ABSTRACT The research aims to (1) analyze significance effect of leadership on employee’s performance; (2) analyze significance effect of the organizational commitment on employee’s performance; (3) analyze significance effect of the collectivism culture on employee’s performance; (4) analyze effect of leadership on employee’s performance moderated collectivism culture; (5) analyze effect of the organizational commitment on employee’s performance moderated collectivism culture. This research uses population research while the population is all employee’s at the CV Pakis Aji in Purwodadi Sub District consist of 45 respondents. Data collecting with questionnaire technique. Results of this research showed that (1) leadership has a significantly effect to employee’s performance (2) organizational commitment has a significantly effect to employee’s performance. (3) collectivism culture has a significantly effect to employee’s performance. (4) collectivism culture has moderate the effect of leadership to employee’s performance. (5) collectivism culture has moderate the effect of organizational commitment to employee’s performance. Keywords: leadership, organizational commitment, collectivism culture, employee’s performance.